2020
DOI: 10.3847/1538-4357/ab64f5
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of the Accretion Disk–Corona during the Bright Hard-to-soft State Transition: A Reflection Spectroscopic Study with GX 339–4

Abstract: We present the analysis of several observations of the black hole binary GX 339-4 during its bright intermediate states from two different outbursts (2002 and 2004), as observed by RXTE/PCA. We perform a consistent study of its reflection spectrum by employing the relxill family of relativistic reflection models to probe the evolutionary properties of the accretion disk including the inner disk radius (R in ), ionization parameter (ξ), temperatures of the inner disk (T in ), corona (kT e ), and its optical dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 115 publications
(163 reference statements)
8
33
0
Order By: Relevance
“…However, we do nonetheless see the continuing evolution of the coronal temperature, from high to low, and most importantly, we have shown that reflection modeling of this kind demonstrates the clear luminosity dependence: a more luminous corona is a cooler corona. Sridhar et al (2020) recently explored the evolution of GX 339−4 in transition from the hard to the soft state, using a similar type of detailed analysis of its reflection properties. They showed that the inner disk radius remains constant during the transition, having approached the ISCO during the bright hard state.…”
Section: The Evolution Of Xte J1550−564mentioning
confidence: 99%
“…However, we do nonetheless see the continuing evolution of the coronal temperature, from high to low, and most importantly, we have shown that reflection modeling of this kind demonstrates the clear luminosity dependence: a more luminous corona is a cooler corona. Sridhar et al (2020) recently explored the evolution of GX 339−4 in transition from the hard to the soft state, using a similar type of detailed analysis of its reflection properties. They showed that the inner disk radius remains constant during the transition, having approached the ISCO during the bright hard state.…”
Section: The Evolution Of Xte J1550−564mentioning
confidence: 99%
“…During the high soft state, the inner disc could extend into the ISCO (Plant, et al 2014). Recently, Sridhar, et al (2020) found that the truncation radius remains low (< 9r g ) throughout the bright intermediate state (i.e., the width of the Fe K emission line is nearly constant throughout this transition indicating a quasi-static truncation radius). The evolution of the accretion disc during the intermediate state then should be driven by the variation in accretion rate rather than by the changes in truncation radius.…”
Section: Discussionmentioning
confidence: 99%
“…also reported this tight correlation in GX 339-4. Sridhar, et al (2020) found that the temperatures of both inner disc and corona are sensitive to the luminosity of state transition.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we consider this not to imprint a significant impact on our results and, if anything, it would enhance the difference between the observed AGN and XRB Γ distributions, strengthening our results. Moreover, Sridhar et al (2020) recently performed a detailed characterisation of the reflection features across the hard-to-soft transition of the 2002 and 2004 outbursts in GX 339−4. With respect to the total of 14 observations they used to sample SS02 and SS04, we only shared five, namely Obs.…”
Section: Possible Biases: X-ray Reflectionmentioning
confidence: 99%
“…The former two in SS02 were defined as SIMSs by Belloni et al (2005) from timing analysis constraints and were included in our selection, while the latter in SS04 were included with our selection criterion following Belloni et al (2006). The remaining states in Sridhar et al (2020) were instead defined either as hard or as hard-intermediate states by Belloni et al, therefore they were not analysed in this work.…”
Section: Possible Biases: X-ray Reflectionmentioning
confidence: 99%